Comparative Efficacy and Potency of Various Extracts of Rhizomes and Leaves of Alpinia allughas - Sethi, Sonali; Prakash, Om; Pant, A.K. (Asian Journal of Chemistry, 2016)
The extract of dried rhizomes and leaves of Alpinia allughas was partitioned with different solvent system by increasing their polarities (petroleum ether, hexane, dichloromethane and methanol). All the extracts were tested for there phytochemical make up and revealed to the presence of secondary metabolites like steroids, terpenoids, alkaloids, glycosides, saponins, phytosterol, etc. The phenolic content and flavonoid content were found maximum 348.18 mg/g GAE (gallic acid equivalent) and 52.82 mg/g CNE (catechin equivalent) quantitatively, respectively in methanolic extracts of leaves, whereas o-dihydric phenol content was found maximum 54 mg/g CLE (catechol equivalents) in rhizomes extract. The results thus revealed that this herb is a big repository of phytochemicals. The greater correlation coefficient among these parameters in leaves as compared to rhizomes of Alpinia allughas indicated the potency of leaves for usage as drug in indigenous system of medicine and for the development new molecules.